BIAS GENDER DALAM PEMILIHAN PRAJURU DESA ADAT TENGANAN PEGRINGSINGAN, MANGGIS, KARANGASEM - Widawan, I Kadek Krisna; Erviantono, Tedi; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2017)
The apad ulu system is a marriage sequence system for structural filling of the Prajuru of Customary Village. Patriarchy is still very inherent in the customary order, like ulu apad. Women seem to just follow the order made the majority by men. The research entitled